2014
DOI: 10.1371/journal.pone.0111227
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Ability Determines the Role of Environmental, Spatial and Temporal Drivers of Metacommunity Structure

Abstract: Recently, community ecologists are focusing on the relative importance of local environmental factors and proxies to dispersal limitation to explain spatial variation in community structure. Albeit less explored, temporal processes may also be important in explaining species composition variation in metacommunities occupying dynamic systems. We aimed to evaluate the relative role of environmental, spatial and temporal variables on the metacommunity structure of different organism groups in the Upper Paraná Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
199
9
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(227 citation statements)
references
References 43 publications
17
199
9
2
Order By: Relevance
“…In contrast to macroinvertebrates, the zooplankton community structure did not significantly change from the dry period to the period after controlled flooding. Zooplankton are generally efficient passive overland dispersers especially over small scales (Havel & Shurin 2004;Padial et al 2014). They produce dormant resting eggs that are accumulated in a persistent egg bank (Brendonck & De Meester 2003) which increases their likelihood of dispersal by wind and animal vectors (Waterkeyn et al 2010;Vanschoenwinkel et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to macroinvertebrates, the zooplankton community structure did not significantly change from the dry period to the period after controlled flooding. Zooplankton are generally efficient passive overland dispersers especially over small scales (Havel & Shurin 2004;Padial et al 2014). They produce dormant resting eggs that are accumulated in a persistent egg bank (Brendonck & De Meester 2003) which increases their likelihood of dispersal by wind and animal vectors (Waterkeyn et al 2010;Vanschoenwinkel et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Water transportation and its role in the studied system As widely recognized for microorganisms (Fontaneto & Hortal, 2012), phytoplankton has a high passive dispersal ability compared to ''bigger'' components of (Padial et al, 2014). Dispersal of phytoplankton can be mediated by a variety of physical (wind and water) and biological vectors (aquatic birds, mammals, insects, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In naturally connected ecosystems such as floodplain lakes and complex river systems, water flow is considered the main dispersal vector and both seasonality (duration) and directionality of river flow, as well as water course distances, have an important role in shaping metacommunity in the different ecosystems belonging to the ''network'' (Liu et al, 2013;Padial et al, 2014;Devercelli et al, 2016). However, in the present study, the network system was formed by human-operated reservoirs and both duration and directionality of water flow were strongly subjected to unpredictable constraints linked to the need of the drinking water supply of urban centers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has indicated that phytoplankton generally respond to environmental factors while zooplankton are more dispersal-limited (Beisner et al 2006, De Bie et al 2012, Padial et al 2014. Such differential response patterns could also interfere with a strong biogeographical coupling of the groups.…”
Section: Introductionmentioning
confidence: 95%